Asupan gizi sebagai faktor risiko penyakit infark miokard akut di Rumah Sakit Sanglah Denpasar - PP Sri Sugiani; Hamam Hadi; I Dewa Putu Pramantara (Jurnal Gizi Klinik Indonesia, 2004)
Background: Coronary heart disease especially acute myocardial infarction (AMI) is one of the main causes of death even in the developing countries. Coronary heart disease has been reported to be associated with high intakes of some nutrients.Objective: The study conducted to understand the role of nutrient intake as risk factors of AMI in Sanglah Hospital, Denpasar.Methods: A case control study was conducted in district of Denpasar in 2003. Cases were people who had AMI and hospitalized in Sanglah Hospital. Each case had two controls one of which was hospitalized patient with no AMI and the second was taken from the case-neighboring household. Controls were sex-and-age matched with cases. Data on nutrient intakes of cases and controls were collected using food frequency questionnaire (FFQ). Data of lipids profile were collected by a chemical analyst. Data on nutrient intakes were analyzed using food processor II (FP II). Multiple logistic regression models were used to examine whether nutrient intakes were risk factors of AMIResults: this study showed that people who had energy intake from fat more than 30% of the total energy were 12 times (OR=12, 95 % CI: 2,71 – 53) more likely to have AMI than those with energy intake < 30%. People with high sodium intake were 9 times (OR=9, 95% CI= 1.8-43.4) more likely to have AMI than those with low sodium intake. People with LDL/HDL ratio more than 3 were 7 times (OR=7, 95% CI= 1.4 – 3.7) more likely to have AMI than those with LDL/HDL ratio less than 3.Conclusion: High fat and sodium intakes and high LDL/ HDL ratio appeared to be risk factors of AMI.